Combined Training of One Cognitive and One Metacognitive Strategy Improves Academic Writing Skills - Wischgoll, Anke (Frontiers in Psychology, 2016)
Academic writing is a challenging task. Expert writers apply various writing skills as they anticipate the reader’s view of their text while paying attention to structure and content. Research in the high school setting shows that the acquisition of writing skills can be supported by single-strategy training. However, research in higher education is scarce. We tested whether the development of academic writing skills can also be effectively supported by training single strategies or even combined strategies. As metacognition is an important skill for advanced and adult learners, we focused in this study on the benefit of combined cognitive strategies with and without a metacognitive strategy. An experiment including three conditions was conducted (N = 60 German-speaking psychology undergraduates, M=22.8, SD=4.4), which lasted for three hours. Each group received a modeling intervention of a basic cognitive strategy on the application of text structure knowledge. Two groups received an additional modeling intervention with either a cognitive strategy treatment on text summarization or a metacognitive strategy treatment on self-monitoring the writing process. One group received no further strategy treatment. Prior knowledge and learning outcomes were measured with a specially developed test on academic writing skills. In addition, all participants wrote an abstract of an empirical article. We found that learners who received the additional self-monitoring strategy intervention benefited significantly more in terms of acquisition of academic writing skills and the quality of their texts than learners who did not receive this intervention. Thus, the results underline the importance of self-monitoring strategies in academic writing. Implications and further research opportunities are discussed.